Donor–Acceptor Oligoimides for Application in High‐Performance Electrical Memory Devices. Issue 7 (27th May 2013) - Lai, Yi‐Cang; Kurosawa, Tadanori; Higashihara, Tomoya; Ueda, Mitsuru; Chen, Wen‐Chang
Abstract Two new oligoimides, OI(APAP-6FDA) and OI(APAN-6FDA), which consisted of electron‐donating N‐(4‐aminophenyl)‐N‐phenyl‐1‐aminopyrene (APAP) or N‐(4‐aminophenyl)‐N‐phenyl‐1‐aminonaphthalene (APAN) moieties and electron‐accepting 4, 4′‐(hexafluoroisopropylidene)diphthalic anhydride (6FDA) moieties, were designed and synthesized for application in electrical memory devices. Such devices, with the indium tin oxide (ITO)/oligoimide/Al configuration, showed memory characteristics, from high‐conductance Ohmic current flow to negative differential resistance (NDR), with corresponding film thicknesses of 38 and 48 nm, respectively. The 48 nm oligoimide film device exhibited NDR electrical behavior, which resulted from the diffusion of Al atoms into the oligoimide layer. On further increasing the film thickness to 85 nm, the OI(APAP-6FDA) film device showed a reproducible nonvolatile "write once read many" (WORM) property with a high ON/OFF current ratio (more than ×104). On the other hand, the device that was based on the 85 nm OI(APAN-6FDA) film exhibited a volatile static random access memory (SRAM) property. The longer conjugation length of the pyrene unit compared to that of a naphthalene unit was considered to be responsible for the different memory characteristics between these two oligoimides. These experimental results suggested that tunable switching behavior could be achieved through an appropriate design of the donor–acceptor oligoimide structure and controllable thickness of the active memory layer.